PSIXOLOG TALABALARNI KASBIY KUTISHLARINING IJTIMOIY-PSIXOLOGIK OMILLARI - Maxammatova, S.S. (SCIENCE and SOCIETY, 2025)
The article explores psychological methods and tools, specific features of the formation of socio-psychological factors of professional expectations of psychologist students. In the socio-psychological process of professional expectations of students in educational activities, scientific approaches, empirical analyzes, methods and tools for determining the factors and conditions for the formation of socio-psychological training for professional activities and improving the effectiveness of the process under study are researched and presented effective recommendations.